Bioaccumulation and Evaluation of Magnesium Oxide Nanoparticles Toxicity and Combination Effects of Vitamin E and C with it on Exposed Male Rats - Majeed, Soma Ismael; Mohammed, Sulaf Mustafa; Mohammad, Ali Mustafa (Kurdistan Journal of Applied Research, 2023)
In the recent years, MgO nanoparticles (MgO NPs) have been one of the metal oxide nanoparticles that used in various medicinal fields. Despite MgO NPs' widespread use, a little is known regarding their cytotoxic effects on health. The purpose of this study was to determine the toxic dose of MgO NPs that prepared by the sol-gel method and the roles of vitamins E and C in the toxicity that is produced by MgO NPs. The MgO NPs were characterized and several amounts (62.5, 125, 250, and 500 mg/kg BW) were orally administrated for 28 days to male Wister rats. Toxic dosimetry was evaluated using metal content analysis, hematological, biochemical, histopathological, and serum ROS estimation. Then toxic doses of MgO NPs were administered orally with vitamins E and C, or a combination of them for six weeks, twice a week. The result showed 500 mg/kg bw/day MgO NPs is considered as a toxic and leads to a significant Mg bioaccumulation in the liver (P < 0.001) and significantly increased serum ROS (P<0.001) and histopathological damage in the liver and kidney with an immunologic response. Administration of vitamin E with MgO NPs significantly increased serum ROS and adversely affected blood parameters and histological damage to the liver and kidney. The combination of vitamins E and C with MgO NPs significantly reduced the immunologic response to MgO NPs, but serum ROS levels increased significantly with histopathological damage in vital organs. Vitamin C significantly reduced MgO NPs-induced damage in kidney and liver tissues. In the conclusion, MgO NPs are toxic at high doses. Administration of vitamin E alone or combined vitamin E and C with toxic doses of MgO NPs increases their toxicity. However, vitamin C was shown to be histopathologically protective. Therefore, a serious caution should be considered when vitamins are administered with nanoparticles.